Bouquet as an Alternative Homemade Creative Business - Nuryana, Ida; Ruspitasari, Widi Dewi; Andarsari, Pipit Rosita (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This project explores the potential of a homemade bouquet business that offers long-lasting, sustainable gift options. Targeting students and young professionals, it provides an alternative to traditional flowers that wilt quickly, promoting creativity and eco-friendly gifting. Method: The bouquets are made from non-perishable materials, such as artificial flowers and fabric, to ensure longevity. A segmentation, targeting, positioning, pricing, and promotional strategy is used to reach the target market. Promotion is carried out primarily on social media platforms like Instagram and Facebook, with personal selling techniques for local engagement. Practical Application: This project fosters local entrepreneurship, supports young people in developing business skills, and encourages sustainable gifting practices. It also creates local employment and drives innovation in product design and marketing. Conclusion: The project meets the target market's needs by offering creative, affordable bouquets. Through online marketing and personalized selling, it promotes sustainability and entrepreneurship, contributing to both economic and social development.